INVESTMENT GALLERY ROLE IN MODERATING FINTECH, FINANCIAL LITERACY, AND RISK TOLERANCE ON STOCK INVESTMENT DECISIONS - Rina Susanti; Dorothea Ririn Indriastuti (Universitas Tulungagung, 2026)
Stock investment has become increasingly popular among university students. This trend is driven by the role of the Indonesia Stock Exchange (IDX) in providing education and Investment Gallery facilities across various universities. These galleries serve as practical hubs for students to gain hands-on knowledge, enabling them to understand the mechanisms of the stock market and the practicalities of investing. This development is particularly relevant given the rapid advancement of technology and the ease of access to online trading platforms. Students who are well-educated both in theory and practice are expected to become the stock investors of the future. This is crucial for increasing the number of retail investors in Indonesia, which remains significantly lower in percentage compared to more developed nations. Consequently, this study aims to determine whether financial technology, financial literacy, and risk tolerance significantly influence investment decisions. Furthermore, it examines whether Investment Gallery educational facilities act as a moderator that strengthens or weakens the impact of financial technology, financial literacy, and risk tolerance on investment decisions.